Drug-related problems in home-dwelling older adults: a systematic review - Plácido, Ana I. (2021)
Purpose:The complex combination of medicinesassociated with age-related physiological alterationsleads older adults to experience drug-relatedproblems (DRPs). The goal of this study was toreview the frequency and type of DRPs and DRP riskfactors in home-dwelling older adults.Methods:A MEDLINE PubMed and EMBASEscientific databases search was performed. Articlespublished from January 2000 through December2018 reporting DRPs in home-dwelling older adultswere included.Findings:From 668 articles screened, 13 met theinclusion criteria and were included in this study.Overall, the studies included 8935 home-dwellingpatients. The mean number of DRPs per patientobserved was 4.16 (1.37e10). The main causes ofDRPs were“drug selection”(51.41%),“dose selection”(11.62%), and“patient related”(10.70%) problems.The drug classes more frequently associated withDRPs were“cardiovascular system,”“alimentary tractand metabolism,”and“nervous system,”and theyrepresented 32.1%, 29.4%, and 16.5% of all drugselection problems, respectively. Respiratory systemmedicines accounted for 6.65% of all DRPs, of which“patient related”problems accounted for 97.28%.Implications:Despite the heterogeneity ofmethodology of the included studies and theheterogeneity of tools used to identify DRPs, thisanalysis clearly shows the high prevalence of DRPs inhome-dwelling older adults and highlights the needfor interventions to improve medicine use in thispopulation. This work also provides usefulinformation for the development of strategies toimprove medication use in home-dwelling olderadults.